-6x+13=13

Simple and best practice solution for -6x+13=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+13=13 equation:


Simplifying
-6x + 13 = 13

Reorder the terms:
13 + -6x = 13

Add '-13' to each side of the equation.
13 + -13 + -6x = 13 + -13

Combine like terms: 13 + -13 = 0
0 + -6x = 13 + -13
-6x = 13 + -13

Combine like terms: 13 + -13 = 0
-6x = 0

Solving
-6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 5(-9)+7t=-35 | | 5x-10=2(3x+2) | | 6m+7(7+5m)=2m-37 | | 3(-5x-4)+2(-4x+1)= | | 5x-3/4=2 | | 2(3x+7)=-4(3-2x) | | x^2-14-2=0 | | 12+4x=-2x-6 | | 12(t+4)=15(3t+1) | | -5x+8=38 | | -3x+10-x=-2x-8 | | 4(4x+2)=2(8x+4) | | 3(2x-1)+3x=-20+71 | | -5(6-2x)=80 | | d^2-9d+8=0 | | 7(x+10)=56 | | 85-5x=13x+17 | | p^2-8p=0 | | 77-6x=12x+17 | | 9z-5=9 | | 154=-7(-1+3n) | | 11-7x=106-42x | | 7(-7+x)=28 | | 12x+7-2x+6=7(2x-5) | | 7a^2+9a=0 | | -2(t-4)+8t=4t-2 | | 41=52-4m | | 24x^2=2-13x | | 4(5x-7)=212 | | 2x^2-12*x+9=0 | | 4x+8=2(x+1) | | 5(a-5)=60 |

Equations solver categories